Emphasizing the Working Capital Management and Firms’ Profitability: Evidence from Quoted Firms on the Nigerian Stock Exchange - Oladipupo, Olaoye Festus; Olatunbosun, Falana (New Ideas Concerning Science and Technology Vol. 4, 2021)
Over the years, it appeared that firms failed to subject short-term investments to proper management thereby leading to either excessive or inadequate working capital which in turn affected their profitability. Working capital and the sequence it forms are managed by working capital management. To empirically satisfy this, this paper examined working capital management and firms’ profitability in Nigeria quoted firms on Nigerian Stock Exchange (NSE). A panel data methodology was used with different regression estimators to analyze this relationship based on a balanced panel of 10 listed firms during the period 2008-2017. It was discovered that cash collection period and cash payment period exerted a negative impact on return on assets, though the impact was only significant for cash payment period on the ground of ?0.064 (p = 0.000 < 0.05), as against the estimate for cash collection period that stood at ?0.032 (p = 0.077 > 0.05). Also discovered was that both the current ratio and inventory period exerted a positive impact on return on assets, though the impact was only significant for current ratio on the ground of 8.172 (p = 0.000 < 0.05), as against the estimate for inventory period that stood at 0.045 (p = 0.438 > 0.05). The study concluded that working capital management affected firms’ profitability in Nigeria. Therefore it was recommended that while the shorter collection was maintained, payment to creditors should not be elongated so as to enjoy cash discount (if any) and that firms should be proactive in the management of raw materials in order to avoid idle resources that might negatively impact their financial performance. Finally, the researcher recommends conducting further studies and researches on working capital management and firms’ profitability in the banking sector.